Influence of processing and external storage conditions on the performance of envelope materials for stratospheric airships. Issue 1 (1st January 2021) - Lv, Jing; Zhang, Yuanping; Gao, Heng; Zhang, Taihua
Highlights: Properties of envelope materials are processing and storage conditions dependent. Pressing at 200 °C led to helium leakage and sharp reduction of tensile strength. Flexing renders polymer layers worn off and damages the properties of samples. UV radiation and ozone lead to dramatic reduction in performance of samples. Abstract: Envelope materials are extremely vital for stratospheric airships, which are widely used in numerous applications. The influence of processing as well as the storage and utilization conditions on the performance of envelope materials has been studied systematically for the first time. Results show that the performance of envelope materials depends largely on the hot-pressing temperature and the flexing during processing. The tensile strength of samples dropped to 289.1 ± 8.0 MPa from 346.6 ± 9.3 MPa when pressed at temperature above 180 °C and helium leakage appeared. The outer layers would be worn off when flexed no matter by manual or machine, resulting in dramatic increase of helium permeability and even leakage as well as varying decrease of mechanical properties. Hence, suitable hot-pressing temperature and limitation of flexing as little as possible during processing are essential to obtain products with suitable properties. Besides, the storage and utilization conditions are also critical to the properties of envelope materials. Both naturally aged samples in outdoor storage on ground and samples recovered from actual flight on stratospheric airship exhibited reduced mechanical properties and even helium leakage due to excess solar irradiation, ozone concentration and energetic particles interaction compared with those stored indoors. The weatherability of envelope materials should be further strengthened in the next few years. This research could provide a theoretical guidance for actual practice.